(untitled) (Research, Society and Development, 2024)
Introduction: The group of inflammatory bowel diseases (IBD) has two main representatives: Crohn’s Disease (CD) and Ulcerative Colitis (UR). IBD has a chronic, inflammatory and autoimmune nature, with a heterogeneous and difficult to differentiate clinic, marked by diarrhea, fever and abdominal pain. Objective: to analyze, in a quantitative and temporal way, the epidemiological characteristics of Crohn’s Disease and Ulcerative Colitis from January 2012 to August 2023. Methodology: a literature review was carried out, based on scientific articles from Scielo and Pubmed , using the descriptors Crohn’s disease, ulcerative colitis and ileocolitis. Articles in Portuguese were included, published between 2000 and 2023. Furthermore, a descriptive cross-sectional epidemiological study was carried out based on the SUS health information department (DATA/SUS) between January 2012 and August 2023, using the variables: hospital admissions, mortality rate, deaths, age group, color/race, sex, nature of care and health macro-region, average hospital stay. Conclusion: it was noted that IBD has been increasing in prevalence since the second half of the 20th century, presenting a long and relapsing clinical course and, therefore, representing an important public health problem.